2024
DOI: 10.1097/md.0000000000037037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of uncut Roux-en-Y and Billroth II anastomosis in gastrointestinal reconstruction following laparoscopic radical gastrectomy for distal gastric cancer

Bufei Zhao,
Zhun Yu,
Ting Hu

Abstract: This study retrospectively analyzed the clinical efficacy of Uncut Roux-en-Y and Billroth II anastomoses in gastrointestinal reconstruction following laparoscopic D2 radical gastrectomy for distal gastric cancer. The primary objective was to compare the postoperative outcomes, including quality of life and complication rates, between the 2 surgical techniques. One hundred patients diagnosed with distal gastric cancer were enrolled between June 2020 and May 2023. Patients underwent laparoscopic D2 gastrectomy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Fourteen days after the surgery, individuals in the observation group exhibited a significant decrease in TCM syndrome scores and a significantly higher KPS score compared with the control group. Previous research[ 11 ] has suggested that surgical procedures can deplete qi and impair blood circulation, resulting in decreased postoperative vital energy. Moreover, according to the modern TCM belief[ 12 ], surgery can damage the viscera and veins, leading to abnormal spleen and stomach functions and impaired transport and conduction abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen days after the surgery, individuals in the observation group exhibited a significant decrease in TCM syndrome scores and a significantly higher KPS score compared with the control group. Previous research[ 11 ] has suggested that surgical procedures can deplete qi and impair blood circulation, resulting in decreased postoperative vital energy. Moreover, according to the modern TCM belief[ 12 ], surgery can damage the viscera and veins, leading to abnormal spleen and stomach functions and impaired transport and conduction abilities.…”
Section: Discussionmentioning
confidence: 99%